Role playing vs RPGs as teaching strategies in educational procedure - Gatsakou, Christina; Bardis, Nikolaos; Drigas, Athanasios (Technium Social Sciences Journal, 2021)
The aim of this paper is to shed new light on an innovative teaching strategy and specifically presents the comparison between the use of Role Playing and the use of Role-Playing Games (RPGs) in the educational procedure emphasizing on the unique characteristics of the latter. I will present the theoretical framework of Role Playing and RPGs as well as their benefits and characteristics, concluding to their substantial difference.